Constructing real-time, wash-free, and reiterative sensors for cell surface proteins using binding-induced dynamic DNA assembly1. Issue 10 (14th October 2015) - Tang, Yanan; Wang, Zhixin; Yang, Xiaolong; Chen, Junbo; Liu, Linan; Zhao, Weian; Le, X. Chris; Li, Feng
<x xml:space="preserve">Abstract</x> A real-time, wash-free, and reiterative sensor is constructed for monitoring cell surface proteins using the principle of binding-induced DNA dynamic assembly.